Telemorphosis: Theory in the Era of Climate Change, Vol. 1 - Cohen, Tom (Critical Climate Change, 2012)
The writers in the volume ask, implicitly, how the 21st century horizons that exceed any political, economic, or conceptual models alters or redefines a series of key topoi. These range through figures of sexual difference, bioethics, care, species invasion, war, post-carbon thought, ecotechnics, time, and so on. As such, the volume is also a dossier on what metamorphoses await the legacies of -humanistic- thought in adapting to, or rethinking, the other materialities that impinge of contemporary -life as we know it.- With essays by Robert Markley, J. Hillis Miller, Bernard Stiegler, Justin Read, Timothy Clark, Claire Colebrook, Jason Groves, Joanna Zylinska, Catherine Malabou, Mike Hill, Martin McQuillan, Eduardo Cadava and Tom Cohen.